Visit‐to‐visit blood pressure variability is associated with functional decline in older adults: The S.AGES cohort: Epidemiology: Cardiovascular risk factors. (7th December 2020) - Rouch, Laure; Vidal, Jean‐Sébastien; Hanon, Olivier; ,
Abstract: Background: Visit‐to‐visit blood pressure variability (BPV) has been increasingly recognized as a predictor of cardiovascular events, all‐cause mortality and more recently of cognitive decline and dementia. All these associations may be mediated by vascular damage which is a determinant of functional decline in older adults. We aimed to investigate the impact of visit‐to‐visit systolic, diastolic, mean arterial pressure and pulse pressure variability on functional decline in non‐institutionalized patients aged ≥ 65 years. Method: 3042 subjects from the S.AGES (elderly subjects) cohort underwent clinical examinations every 6 months during 3 years. Systolic, diastolic, mean arterial pressure and pulse pressure variability were evaluated using standard deviation, coefficient of variation, average real variability, successive variation, variation independent of mean and residual standard deviation. Functional decline was assessed using the Activities of Daily Living (ADL) and Instrumental Activities of Daily Living (IADL) scales and defined over time as any help required to perform at least one task. Cox proportional hazards models were used for the analyses. Result: Among the 3042 subjects, 527 (17.3%) had functional decline (ADL) over time. After adjustment for demographics, systolic blood pressure, antihypertensive drugs, coronary artery disease, diabetes mellitus, chronic heart failure, atrial fibrillation, transient ischemic attack or stroke, smoking, dyslipidemia and Mini Mental State Examination at baseline, higher systolic blood pressure variability was associated with greater risk of functional decline (ADL) (adjusted HR per 1‐SD increase of coefficient of variation = 1.12, 95% CI [1.03‐1.22], p<0.01). Similar results were observed for diastolic blood pressure variability (adjusted HR = 1.11, 95% CI [1.01‐1.22], p=0.03) and mean arterial pressure variability (adjusted HR = 1.15, 95% CI 1.05‐1.25, p<0.01). Higher pulse pressure variability was no longer significantly associated with functional decline after adjustment for age (p=0.6). Similar patterns were found with all indicators of variability and loss of autonomy defined using IADL. Conclusion: Higher blood pressure variability could be a novel risk factor for functional decline and controlling blood pressure instability a promising interventional target in preserving autonomy in older adults.